Identifikasi Adverse Drug Reactions Penggunaan Obat Anti Tuberkulosis Paru Pada Pasien Di Salah Satu Puskesmas Kota Batam - Reny Haryani; Farina; Mawardi Badar (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
Adverse Drug Reactions (ADRs) are commonly encountered, particularly among tuberculosis (TB) patients undergoing long-term therapy involving multiple drug combinations. Monitoring ADRs is essential to ensure treatment safety and enhance patients' quality of life. This study aimed to evaluate the incidence of ADRs in pulmonary TB patients undergoing treatment at a public health center (Puskesmas) in Batam City. An observational study with a cross-sectional design was employed. A total of 58 newly diagnosed pulmonary TB patients in the intensive treatment phase who met the inclusion criteria participated as respondents. These criteria included being in late adolescence to late elderly age, willingness to participate, and having complete medical records. Data were collected using structured questionnaires and medical record reviews, and analyzed using the Naranjo algorithm to assess the likelihood of ADRs being related to anti-TB medication use. The results showed that most respondents were male (72.41%), predominantly within the productive age group. All patients received the RHZE regimen. The most frequently reported adverse effects were reddish discoloration of urine (100%), joint pain (19%), and gastrointestinal disturbances (15.5%). Based on the Naranjo algorithm, the majority of cases were classified as “Probable” (62.07%). These findings highlight the importance of systematic ADR monitoring and patient education to support treatment success.